Best practices for promoting teachers’ professional development in Malaysia - Salleh, Mohamad Johdi; Hatta, Muhammad (University Malaysia Terengganu, 2019)
The cluster schools in Malaysia were formed to employ best teachers to achieve educational outcomes corresponding to 4th Industrial revolution. This study examines the best practices of promoting teachers’ professional development among principals of cluster secondary schools in Malaysia. The Principal Instructional Management Rating Scale (PIMRS) was used as the data collection instrument through survey questionnaire. A diverse sample constituting 871 respondents of different gender, ethnicity, type of schools, and, designations at schools was drawn randomly using cluster sampling. The researcher employed descriptive statistical procedures involving frequency count, percentage distribution, and, means to analyze the data collected. Use of such data is one of the standard practices in Malaysia to plan for the professional development among principals of cluster secondary schools. The study indicated that the best practice of developing teacher professionalism among principals of cluster secondary schools Malaysia according to principals’ and teachers’ perceptions was ‘setting aside time at faculty meetings for teachers to share ideas on instruction or information from in-service activities.’ Findings shall effectively assist the process of promoting a positive school learning climate among the principals and teachers of secondary schools in Malaysia in wake of meeting the goals of National Philosophy of Education, Vision 2020 and aspiration of the Malaysia Education Development Plan 2013-2025 in the Era of IR 4. Other school principals may use the outcomes of research to facilitate and improve students' academic performance in their respective schools and join hands in the collective effort of raising the work force compatible to meet national goals at par with international standards.